A Self-Adaptive Inertia and Damping Combination Control of VSG to Support Frequency Stability - Dongdong Li; Qianwei Zhu; Shunfu Lin; Bian, X. Y. (IEEE transactions on energy conversion, 2017)
In the virtual synchronous generator (VSG) field, the traditional methods, such as the constant parameters control method and the self-adaptive inertia control method, always neglect the effect of the damping factor. This letter proposes a self-adaptive inertia and damping combination control method to improve the frequency stability with an interleaving control technique. Tests on the MATLAB/Simulink VSG model demonstrate the effectiveness of the proposed method.